2021
DOI: 10.1007/s11920-021-01286-0
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Exacerbations of Mood Disorders: Findings and Knowledge Gaps

Abstract: Purpose of Review In contrast to premenstrual dysphoric disorder (PMDD), premenstrual exacerbations (PMEs) of ongoing mood disorders are understudied. The aim of this review is to describe diagnostic issues, epidemiology, underlying mechanisms, and treatment for PME in unipolar depression and bipolar disorder, and to discuss clinical and research implications. Recent Findings Community-based and clinical studies estimate that in women with mood dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 96 publications
0
13
0
1
Order By: Relevance
“…This is important because it was suggested that the old tests that were developed for males, such as the elevated plus maze, may not be applicable to females as they cannot re-create increased female risk for anxiety disorders reported in humans [23,41]. What we demonstrate, though, is that proper classification of females will show the same trend that we see in humans, which is that low-estrogenic female mice (diestrus) show higher anxiety indices than highestrogenic females (proestrus) and males, thus recreating the fact that sex hormone withdrawal in humans is a trigger for increased anxiety and depression symptoms [8,9] or other reproduction-related disorders such as PMDD [10], postpartum depression [11,12], and perimenopausal depression [8,14]. At the structural level, this vulnerability is seen as a drop in dendritic spines in the mouse ventral hippocampus following estrogen withdrawal; a similar finding is also reported in humans as reduced hippocampal gray matter following an estrogen drop [2,42].…”
Section: The Estrous Cycle Tracking Is a Stressor And May Represent A...mentioning
confidence: 68%
See 2 more Smart Citations
“…This is important because it was suggested that the old tests that were developed for males, such as the elevated plus maze, may not be applicable to females as they cannot re-create increased female risk for anxiety disorders reported in humans [23,41]. What we demonstrate, though, is that proper classification of females will show the same trend that we see in humans, which is that low-estrogenic female mice (diestrus) show higher anxiety indices than highestrogenic females (proestrus) and males, thus recreating the fact that sex hormone withdrawal in humans is a trigger for increased anxiety and depression symptoms [8,9] or other reproduction-related disorders such as PMDD [10], postpartum depression [11,12], and perimenopausal depression [8,14]. At the structural level, this vulnerability is seen as a drop in dendritic spines in the mouse ventral hippocampus following estrogen withdrawal; a similar finding is also reported in humans as reduced hippocampal gray matter following an estrogen drop [2,42].…”
Section: The Estrous Cycle Tracking Is a Stressor And May Represent A...mentioning
confidence: 68%
“…Ovarian hormone fluctuation shapes brain physiology [1][2][3][4][5][6][7] and represents a major psychiatric risk factor in humans [8][9][10][11][12][13][14], yet this variable is largely ignored in preclinical neuroscience research, clinical studies, and psychiatric practice [8,[15][16][17]. The psychiatric risk in women is elevated throughout the reproductive period and is directly linked to hormonal changes [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The profile of symptoms is similar throughout the cycle but the intensity is significantly greater in the premenstrual phase” [ 38 ]. Previous reviews on this topic have highlighted the various methodological flaws of previous studies, which led to over- or underestimates of the prevalence of premenstrual exacerbation of mood disorders [ 39 , 40 ]. Notwithstanding these methodological limitations, available evidence suggests that premenstrual exacerbation may occur in 44–68% of individuals with mood disorders [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sex-steroid milieu changes have been found to alter brain biology, including hippocampal plasticity ( Barth et al, 2016 ; Taylor et al, 2020 ) and serotonergic neurotransmission ( Barth et al, 2015 ), both crucial to maintaining mental health ( Frokjaer, 2020 ). In addition, mental disorders, such as anxiety and mood disorders, can be exacerbated during certain menstrual cycle phases, including premenstrual symptom worsening ( Pinkerton et al, 2010 ; Green and Graham, 2022 ; Kuehner and Nayman, 2021 ). Hormonal fluctuations across the menstrual cycle putatively trigger severe depressive symptoms in some women, i.e., premenstrual dysphoric disorder (PMDD), which can be treated with specific OCs but worsened by others ( Rapkin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%